Elevated urinary IL-36γ in patients with active lupus nephritis and response to treatment. (May 2021) - Majumder, Sanjukta; Singh, Pratibha; Chatterjee, Rudrarpan; Pattnaik, Sarit Sekhar; Aggarwal, Amita
Introduction: IL-36 is a new member of the IL-1 family with pro-inflammatory properties. Serum levels of IL-36 are elevated in patients with Systemic Lupus Erythematosus (SLE). However, no data is available on urinary levels of IL-36 in Lupus Nephritis (LN). In psoriasis expression of IL-36 is site specific and expressed in skin. Hence, we studied urinary levels of IL-36 cytokines in SLE patients. Methods: A total of 196 patients with SLE [97 active LN patients (ALN), 42 inactive LN (ILN) and 57 active lupus patients with no renal involvement (ANR)] and 25 healthy subjects were recruited for the study after obtaining informed consent. Urinary and plasma IL-36α, IL-36γ and IL-36Ra levels were measured by ELISA. Results: Out of 196 patients 178 were females. Urinary IL-36γ levels in SLE patients [0(14.3) pg/ml] were significantly higher than healthy controls [0(0) pg/ml, (P < 0.01)]. Patients with ALN [0(40.6) pg/ml] had significantly higher IL-36γ when compared to ANR [0(0) pg/ml] as well as ILN [0(0) pg/ml]. Urinary IL-36γ levels in ALN patients had a fair correlation with renal SLEDAI (r = 0.26, P = 0.004).The levels reduced significantly post 3 months in patients with ALN. No inverse relationship was noted between IL-36Ra and IL-36α/IL36γ levels. Conclusion: Urinary IL-36γ is produced locally in kidney, correlates with renal disease activity and reduces upon treatment, suggesting that it may have a role in pathogenesis of LN.